Consequences of the catastrophic wildfire in 2020 for the soil cover of the Utrish State Nature Reserve - Kamil Kazeev; Valeria Vilkova; Aslan Shkhapatsev; Olga Bykhalova; Yana Rudenok; Мikhail Nizhelskiy; Sergey Kolesnikov; Tatiana Minkina; Svetlana Sushkova; Saglara Mandzhieva; Vishnu D Rajput (Universitas Sebelas Maret, 2022)
Present work aimed to assess the impact of pyrogenic effect on the flora, and quality and health of soils of the Utrish Reserve. Studies performed on the territory of reserve within a month after the fire revealed that the areas showed varying degrees of damaged characteristics due to catastrophic fire. The entire damage was recorded in a 40-hectare region, while the vegetation on another 26 hectares of the reserve was damaged to a lesser extent. In total, 4,800 trees were eliminated, 73% of them belonged to rare and endangered species, such as Junipers (Juniperus spp.), Mt. Atlas mastic trees (Pistacia mutica), and Pitsunda pines (Pinus brutia var. pityusa). In the areas of severe disturbance, the soil surface was covered with a constant layer of ash two weeks after the fire. As a result, there was an increase in the pH values, and the chemical composition of brown soil (Cambisol) was determined after the fire. There was also an increase in the organic carbon content and peroxidase activity. Catalase activity, which is sensitive to pyrogenic effects, decreased in all soil samples obtained at post-pyrogenic areas. The effect of fire on the biological state of soils may diminish over time, however, the restoration of the damaged ecosystems may take hundreds of years. The results of this study can be used in assessing the damage to ecosystems after the wildfires, as well as in developing methods to accelerate the restoration of soils after a fire impact.